A little care - Loh, Hinako Jinyu (Nanyang Technological University, 2023)
A Little Care is a 3D third-person exploration-puzzle game where you play as Carol, a little girl who tries to recover Grandma's memories of her youth. It is up to you to find the missing stories in Grandma’s old diary, to help her recall her life’s memories!